(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Menstruation is an important physiological function of the female reproductive system. The absence of menstruation is called amenorrhea. Many genetic and nongenetic causes are responsible for primary or secondary amenorrhea. This study aimed to determine the types chromosomal abnormalities among patients with primary or secondary amenorrhea. Methods: It was a cross-sectional study conducted in the Department of Pathology, Bangabandhu Sheikh Mujib Medical University, Dhaka, from September 2019 to August 2021. A total of 115 women who had come for a karyotype test with complaints of pathological amenorrhea were purposively selected. One hundred five cases presented with primary amenorrhea, and 10 cases presented with secondary amenorrhea. Karyotype analysis in peripheral blood by G-banding was carried out using the standard method. Results: Among the 105 patients with primary amenorrhea, 53.3% of patients had a normal karyotype (46, XX), and 46.6% had chromosomal abnormalities (numerical or structural). Turner syndrome classic, 45, XO (16.2%) and 46, XY DSD (Disorders of Sexual Development) (11.4%) were the two most frequent chromosomal abnormalities found in the patients with primary amenorrhea. Among the 10 cases with secondary amenorrhea, seven patients had normal karyotype, and three patients had chromosomal abnormalities (2 had sex chromosomal abnormalities, and 1 had a structural abnormality of autosome). Conclusion: The study of chromosomal abnormalities will help in the early and accurate diagnosis of the underlying aetiology of primary or secondary amenorrhea. It will also help in the management and proper counselling of cases.